Construção de um framework para implementação do lean office no setor administrativo de cooperativas - Martinello, Larissa Maria (2025)
Cooperatives, like commercial companies, seek to improve their operational development to offer quality services and increase the efficiency of their processes. This business segment plays an essential role in the global economy, promoting cooperation among members and driving sustainable economic and social development. However, operational challenges in administrative activities can compromise their efficiency and competitiveness. Lean Office emerges as an effective approach to improve processes and reduce waste in administrative environments. In view of this, this study proposes a specific framework for implementing Lean Office in the cooperative context. To build the framework, a comprehensive review of the literature on Lean Office principles and their applications was carried out, in addition to an analysis of the main characteristics of cooperative systems. Following the steps of the Design Science Research methodology, semi-structured interviews were conducted with two professionals from each of the three cooperative segments – health, credit and agribusiness – who had prior knowledge of the Lean philosophy and experience in cooperative management. The choice of these segments is based on the availability for data collection and their economic relevance in the scientific region. Based on the collected insights and the concepts of Lean Office, a framework was developed that connects its principles to the specificities of cooperatives. The proposal was evaluated through interviews with two experts, one from each segment, validating its solutions. In addition, the research of agreements helps to ensure the application of each waste pointed out by the interviewees, as well as its causes. To demonstrate its applicability, the study presents an implementation roadmap considering the particularities of each segment. This study contributes with a practical and structured framework to guide cooperative managers in the adoption of Lean Office, optimizing administrative processes. In addition, the research enriches the academic literature by offering an initial scientifically based model, helping researchers in the application and advancement of studies on Lean Office in the cooperative context.